2012
DOI: 10.1371/journal.pone.0032432
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Like Effects of the Neonicotinoid Insecticides Acetamiprid and Imidacloprid on Cerebellar Neurons from Neonatal Rats

Abstract: BackgroundAcetamiprid (ACE) and imidacloprid (IMI) belong to a new, widely used class of pesticide, the neonicotinoids. With similar chemical structures to nicotine, neonicotinoids also share agonist activity at nicotinic acetylcholine receptors (nAChRs). Although their toxicities against insects are well established, their precise effects on mammalian nAChRs remain to be elucidated. Because of the importance of nAChRs for mammalian brain function, especially brain development, detailed investigation of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
185
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(193 citation statements)
references
References 52 publications
7
185
0
1
Order By: Relevance
“…One potential mechanism of imidacloprid may be impairing insulin receptor substrate-1 (IRS-1) activation via calcium-dependent mechanisms. This is based on the fact that [i] imidacloprid is reported to increase oxidative stress, [ii] it increases intracellular calcium similar to other agonists of nicotinic acetylcholine receptors, and [iii] both of these effects are known to be associated with insulin resistance by impairing IRS-1 activation (Draznin, 1993;Zemel et al, 1995;Li et al, 2000;Kimura-Kuroda et al, 2012;Cui et al, 2013). It is further supported in a report by Tomizawa and Casida (2002) that desnitro-imidacloprid, an imidacloprid metabolite, activates nicotinic receptors via an intracellular calcium dependent mechanism (Tomizawa and Casida, 2002).…”
Section: Resultsmentioning
confidence: 94%
“…One potential mechanism of imidacloprid may be impairing insulin receptor substrate-1 (IRS-1) activation via calcium-dependent mechanisms. This is based on the fact that [i] imidacloprid is reported to increase oxidative stress, [ii] it increases intracellular calcium similar to other agonists of nicotinic acetylcholine receptors, and [iii] both of these effects are known to be associated with insulin resistance by impairing IRS-1 activation (Draznin, 1993;Zemel et al, 1995;Li et al, 2000;Kimura-Kuroda et al, 2012;Cui et al, 2013). It is further supported in a report by Tomizawa and Casida (2002) that desnitro-imidacloprid, an imidacloprid metabolite, activates nicotinic receptors via an intracellular calcium dependent mechanism (Tomizawa and Casida, 2002).…”
Section: Resultsmentioning
confidence: 94%
“…In animals, exposure to a high dose of imidacloprid may be associated with degenerative changes in thymus, bone marrow, and pancreas [1]. A study conducted in rats suggests that imidacloprid may adversely affect brain development [3]. Recent research suggests that widespread agricultural use of imidacloprid and other pesticides may be contributing to honey bee colony collapse disorder, the decline of honey bee colonies in Europe and North America observed recently [4,5].…”
mentioning
confidence: 99%
“…In a study by Abu-Donia et al (13), IMI increased AChE activity in newborn Sprague-Dawley rats via maternal exposure, and the authors suggested that this induction occurred due to apoptotic events via cellular Ca 2+ -uptake. In another study (48), neonicotinoid insecticides acetamiprid and IMI induced cellular Ca 2+ uptake via α 7 nAChRs in Sprague-Dawley rat cerebellar cell line, and Ca 2+ uptake was inhibited by α-bungarotoxin, a specific α 7 nAChR antagonist. Yeboah et al (49) suggest that α 7 nAChRs, which are constitutively expressed in the kidney of SpragueDawley rats, are highly permeable to Ca 2+ ions.…”
Section: Sex-and Duration-specific Effects Of Imi In Rat Liver and Kimentioning
confidence: 94%
“…Duzguner and Erdogan (16) believe that higher plasma Ca 2+ concentrations could be responsible for the induction of ROS-generating enzymes xanthine oxidase and myeloperoxidase in the liver and brain of female Wistar rats treated with IMI intravenously. Kimura-Kuroda et al (48) have suggested that mammalian ACh receptors are affected by IMI exposure because of conformational changes of the receptor induced by ACh. We therefore believe that higher tChE activity that lowers ACh-assisted IMIbinding may be an adaptive response to oxidative stress induced by elevated Ca 2+ uptake.…”
Section: Sex-and Duration-specific Effects Of Imi In Rat Liver and Kimentioning
confidence: 99%